Electro-optic properties of (100)-oriented (Pb,La(Zr,Ti)O3 thin film - Zhu, Min Min (2013)
(100)-oriented PLZT ((Pb1-x, Lax) (Zry,Ti1-y)1-x/4O3, x/y=9/65) films of up to ~ 1.23 μm have been developed on LaAlO3 single crystal substrate by magnetron sputtering. The as-grown PLZT thin films exhibit high optical transparency in visible and near-infrared light wavelength and high quadratic (Kerr) EO coefficients. Prism coupler measurements reveal that the PLZT thin films possess large refractive index, as high as 2.524 in TE model and 2.481 in TM model. The transparency of >70% in the range of λ= 500-1200 nm, the optic band gap of 3.42 eV and the quadratic electro-optic (EO) coefficient of 3.38 x 10-17 (m/V)2 have been measured in the films. Due to the large EO coefficient and the micrometric thickness, the as-developed PLZT films have great potential in developing longitudinal-or transverse-type EO devices in electric and optic field.